Replacing pet plastic with pla as a sustainable alternative to functional drink containers - Canturin Becerra, Camila Sofia (2025)
Polyethylene terephthalate (PET) is a widely used material in container manufacturing, particularly in bottle production. It is characterized by its low cost and widespread availability. However, its improper disposal has significantly exacerbated global plastic pollution. For instance, less than 50% of plastic bottles are recycled. Moreover, studies indicate that this issue has led to a significant accumulation of plastic waste in the oceans, which continues to grow annually and could be considered floating islands of debris. This study proposes replacing PET with polylactic acid (PLA), a biodegradable and biocompatible polymer with suitable properties for bottle production. PLA also has a shorter decomposition time compared to PET, contributing to the reduction of carbon footprint and greenhouse gas emissions. The research methodology included a diagnostic phase to define objectives, identify constraints, and determine variables based on an extensive literature review. The design phase focused on modeling a PLA-based bottle with detailed specifications and innovative structural features. Additionally, experimental evaluations of biodegradability, compressive strength, and tensile strength were conducted to compare PET and PLA. The study incorporated technical standards and engineering protocols to evaluate critical properties such as material permeability and stress behavior. As a result, it was confirmed that PLA exhibits properties that make it a competitive material compared to PET. In conclusion, this research presents a technically viable alternative to PET bottles through the use of PLA, with the potential to significantly mitigate environmental impacts while maintaining the functional requirements of packaging.